Global Perspectives on Educational Innovations for Emergency Situations - Dennen, Vanessa; Dickson-Deane, Camille; Ge, Xun; Ifenthaler, Dirk; Murthy, Sahana; Richardson, Jennifer C. (Educational Communications and Technology: Issues and Innovations, 2022)
This open access book focuses on making the transition from in-person, classroom education to other feasible alternative modes and methodologies to deliver education at all levels. The book presents and analyzes research questions to explore in this arena, including pedagogical issues relating to technological and infrastructure challenges, teacher professional development, issues of disparity, access and equity, and impact of government policies on education. It also provides unique opportunities and vehicles for generating scholarship that helps explain the varied educational needs, perspectives and solutions that arise during an emergency and the different roles educational institutions and educators may play during this time. Developed from a highly successful Presidential Session at the annual meeting of the Association for Educational Communications and Technology (AECT), this edited volume presents AECT and its membership as the premier organization focusing on the provision of educational communications and technology leadership. In addition, it functions as a contemporary document of this global crisis as well as a rich resource for possible future emergency scenarios in the educational arena.